Hybrid-inspired coolant additive for radiator application - Benedict Foo, Jing Siong (2020)
Due to the increasing demand in the industrial application, nanofluids has attracted a considerable attention of researchers in the last few decades. Nanocellulose with water (W) and Ethylene Glycol (EG) addition to coolant for car radiator application exhibits beneficial properties to improve the efficiency of the radiator. Improved efficiency leads to more compact design of the radiator and increase the durability of the engine. The focus of the present work is to investigate the performance of mono or hybrid metal oxide such as Al2O3 and TiO2 with or without plant base extracted nanocellulose (CNC) with varying concentration as a better heat transfer nanofluid as compared to distilled water as radiator coolant. Therefore, the objective of the present work is to improve and create a new radiator coolant based on aluminium oxide and CNC with readily available coolants (EG) and to investigate the erosion of CNC coolant on automotive radiator. The scope of the present work is CNC dispersed in base fluid of EG and W with 60:40 ratio. The volume concentrations such as 0.1, 0.5, and 0.9% of tested samples have been used for further investigation. Comparative heat transfer performance of prepared nanofluids and convection thermal transport fluid has been investigated in the automotive radiator test rig under two different circumstances i.e., with and without the influence of draft fan. Obtained result reveals that heat transfer coefficient, convective heat transfer, Reynolds number, Nusselt number has proportional relation with volumetric flow rate. The highest absorption peak have been noticed in 0.9% volume concentration of TiO2, Al2O3, CNC, Al2O3/TiO2, and Al2O3/CNC nanofluids which indicate the better stability of nanofluids suspension. Better thermal conductivity improvement have been observed for Al2O3 nanofluids in all mono nanofluids followed by CNC and TiO2 nanofluids respectively. Thermal conductivity of Al2O3/CNC hybrid nanofluids with 0.9% volume concentration has been found to be superior to Al2O3/TiO2 hybrid nanofluids. Al2O3/CNC hybrid nanofluid dominates over other mono and hybrid nanofluids in terms of viscosity at all volume concentrations. CNC nanofluids (all volume concentrations) exhibited the highest specific heat capacity than other mono nanofluids. Additionally, in both the hybrid nanofluids, Al2O3/CNC showed the lowest specific heat capacity. The optimized volume concentration from statistical analytical tool was found to be 0.5%. Nanofluid volume concentration with 0.5% (CNC/Al2O3 and CNC) was selected as thermal transport fluid to be compared with convectional EG-W mixture. The experiment result shows that experimental heat transfer coefficient, convective heat transfer, Reynolds number, Nusselt number has proportional relation with volumetric flow rate.